2021
DOI: 10.3389/fmicb.2021.655095
|View full text |Cite
|
Sign up to set email alerts
|

Succession of Bacterial Community During the Initial Aerobic, Intense Fermentation, and Stable Phases of Whole-Plant Corn Silages Treated With Lactic Acid Bacteria Suspensions Prepared From Other Silages

Abstract: The present study was aimed at investigating the bacterial community in lactic acid bacteria (LAB) suspensions prepared from whole-plant corn silage (LAB suspension-CS) and Elymus sibiricus silage (LAB suspension-ES) and the bacterial community succession of whole-plant corn silages inoculated with LAB suspension-CS or LAB suspension-ES during initial aerobic phase, intense fermentation phase, and stable phase. The LAB suspensions were cultured in sterile Man, Rogosa, Sharpe broth at 37°C for 24 h and used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 33 publications
11
54
0
Order By: Relevance
“…Similarly, Ali et al [36] revealed that the microbiota from red clover had a better effect on bacterial community succession and fermentation quality in red clover silage than that from maize and sorghum. In addition, Sun et al [35] also found that the LAB from whole-plant corn silage had a better promotion effect on microbial succession and fermentation of whole-plant corn silage than those from Elymus sibiricus silage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ali et al [36] revealed that the microbiota from red clover had a better effect on bacterial community succession and fermentation quality in red clover silage than that from maize and sorghum. In addition, Sun et al [35] also found that the LAB from whole-plant corn silage had a better promotion effect on microbial succession and fermentation of whole-plant corn silage than those from Elymus sibiricus silage.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that inoculating lucerne or red clover with PFJ prepared from the ensiling material was more effective at improving fermentation parameters detected in the present study. This might be due to the materials prepared for PFJ and silage being collected from the same field, and the LABs in PFJ are more familiar with the physico-chemical properties of the silage [35]. Similarly, Ali et al [36] revealed that the microbiota from red clover had a better effect on bacterial community succession and fermentation quality in red clover silage than that from maize and sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…Processes 2021, 9, 784 2 of 16 of whole-plant corn silage during fermentation process [5,6]. The main bacterial species present in the silage at the end of the process are Lactobacillus acetotolerans, Lactobacillus silagei, Lactobacillus parafarraginis, Lactobacillus buchneri, and Lactobacillus odoratitofui [7].…”
Section: Lactobacillus Dominates the Bacterial Succession And Determines The Fermentation Qualitymentioning
confidence: 99%
“…This indicated that the high moisture content in whole-plant corn before ensiling was not conducive to reducing AN content during fermentation. Whole-plant corn silage after 5 days of ensiling is in a stable fermentation phase according to Sun et al [9]. The pH was less than 4.0 at 5 days and reached the lowest point at 60 days in all the silages except for H_D, which agreed with a previous study [9]; moreover, lactic acid reached a high level (>76 g/kg DM) at 5 days and increased to its peak point at 14 or 45 days; AN content increased to its highest point at 45 days (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-plant corn silage after 5 days of ensiling is in a stable fermentation phase according to Sun et al [9]. The pH was less than 4.0 at 5 days and reached the lowest point at 60 days in all the silages except for H_D, which agreed with a previous study [9]; moreover, lactic acid reached a high level (>76 g/kg DM) at 5 days and increased to its peak point at 14 or 45 days; AN content increased to its highest point at 45 days (Table 1). Ferrero et al [24] also reported reduced pH and increased contents of lactic acid and AN in whole-plant corn silage after 15 days of ensiling.…”
Section: Discussionmentioning
confidence: 99%